Improvement of Pedagogical Technologies of Comprehensive Development of the Personality of Preschool Children on the Basis of Cultural and Creative Approach (Journal of Pedagogical Inventions and Practices, 2023)
The article is devoted to the problem of the comprehensive development of preschoolers on the basis of the improvement of pedagogical technologies of a cultural and creative nature. The purpose of the work is to develop and practically test the pedagogical system of innovative technologies that contribute to the comprehensive development of children in the process of their involvement in cultural and creative activities.